2021
DOI: 10.1158/1078-0432.ccr-20-3063
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Architecture ofEGFRMutation Predicts the Efficacy of EGFR-Tyrosine Kinase Inhibitors in Advanced NSCLC: A Prospective Multicenter Study (NCT03059641)

Abstract: Purpose: Clonal architecture is fundamental for the understanding of cancer biology and therapy; however, multiregional sampling in advanced-stage cancers is not always applicable. This prospective clinical trial was to investigate whether paired tissue and circulating tumor DNA (ctDNA) could describe the clonal architecture of advanced non-small cell lung cancer (NSCLC) and its association with clinical outcome (NCT03059641).Patients and Methods: Paired tumor and plasma ctDNA samples were sequenced by target-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
(51 reference statements)
1
23
0
Order By: Relevance
“…At present, several studies had confirmed that EGFR targeted therapy dramatically improved the prognosis of patients with NSCLC BMs [ 36 , 37 ]. However, concomitant genetic alterations (such as CDKN2A copy number loss) [ 38 ] and the number of EGFR subclones [ 39 ] are associated with worse clinical outcomes in EGFR mutant NSCLC patients under TKIs treatment. In our study, CDKN2A loss and EGFR subclone number were frequently increased in EGFR -CSF patients, which might be one of the reasons for the poor prognosis of LUAD patients with BM.…”
Section: Discussionmentioning
confidence: 99%
“…At present, several studies had confirmed that EGFR targeted therapy dramatically improved the prognosis of patients with NSCLC BMs [ 36 , 37 ]. However, concomitant genetic alterations (such as CDKN2A copy number loss) [ 38 ] and the number of EGFR subclones [ 39 ] are associated with worse clinical outcomes in EGFR mutant NSCLC patients under TKIs treatment. In our study, CDKN2A loss and EGFR subclone number were frequently increased in EGFR -CSF patients, which might be one of the reasons for the poor prognosis of LUAD patients with BM.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity of Nextseq CN500 were 100% when compared with HiSeq3000 and NovaSeq6000. It also shows good performance on clinical practice and research [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Circulating tumor DNA (ctDNA) sequencing was used to calculate genetic mutation and tumor mutation burden (TMB). The TMB was calculated as the number of somatic nonsynonymous single-nucleotide variants (SNVs) and small insertions/deletions per megabase in the coding region ([mutations per megabase [mut/Mb]] with ≥ 0.005 for ctDNA) and by integrated mutation profiling testing of actionable cancer targets within the same gene panel in the samples from the Geneplus database [20][21][22] . The categorization of TMB-high and TMB-low was explained in the preceding paper 17 .…”
Section: Assessment Of Tumor Mutation Burdenmentioning
confidence: 99%